Corporate Social Responsibility and Firm Financial Performance: The Mediating Role of Internal Control Effectiveness under COSO and SOX Frameworks — Evidence from Pakistan - M. Ashraf; Dr. Amanullah Khattak (Journal of Management Science Research Review, 2026)
This study explores the association between Corporate Social Responsibility (CSR) and firm financial performance (FFP) by examining the mediating role of internal control efficacy within the COSO and Sarbanes–Oxley (SOX) structures. Representing upon Stakeholder Theory, Legitimacy Theory, Agency Theory, and the Resource-Based View, the study hypothesized CSR as a multidimensional paradigm encompassing economic, legal, ethical, philanthropic, environmental, stakeholder, and governance responsibilities. A mixed-method methodology is engaged using primary assessment data to quantify CSR observes and internal control efficiency, supplemented by five-year averaged secondary financial data (ROA, ROE, and Tobin’s Q) from firms listed on the Pakistan Stock Exchange. Using multivariate regression and bootstrapped mediation analysis, the study tests whether internal control serves as a governance technique that transforms CSR creativities into outstanding financial results. The conclusions are projected to contribute to the developing literature on sustainable finance and corporate governance by clarifying the internal managerial mechanisms through which CSR enriches firm value in developing markets. The study offers theoretical, managerial, and regulatory suggestions for solidification governance driven CSR in developing economies.